An Infant With Single Ventricle Physiology and Hypoxemia - Taemyn Hollis; Bradley Tilford; Katherine Cashen (MedEdPORTAL, 2015)
Abstract Introduction Systemic to pulmonary artery shunt occlusion is an uncommon presentation to the emergency department (ED) or pediatric intensive care unit (PICU), but it can result in morbidity and mortality if not recognized and treated in a timely fashion. We present a simulation case of a child who presented to a PICU. Methods The module is to be used in a simulation setting (simulation lab or in situ) with an area to gather to debrief after the simulation is finished. The module takes approximately 45 minutes to complete. Upon arrival participants were divided into groups of four to six. Once all of the groups completed the module the case was discussed using the debriefing questions and then the PowerPoint presentation was reviewed. At the end of the case discussion, each learner was evaluated via the evaluation sheet provided. Results Approximately 20 learners completed this module during two separate sessions. This module helped learners to expand their differential diagnosis and management for hypoxemia in a patient with single ventricle physiology. After this module, learners were also able to recognize the importance of evaluating for the presence of a shunt murmur and steps to take in reestablishing shunt patency. ED residents and ED fellows both gave positive feedback for this module. They verbalized that they felt more confident in their understanding and had increased comfort in caring for a single ventricle patient after completing this module. Discussion This is an excellent case to teach learners how to recognize a patient with systemic to pulmonary artery shunt occlusion and review appropriate management. This module has been used with pediatric residents, cardiovascular surgery nurse practitioners, pediatric emergency medicine fellows, and pediatric intensive care fellows.